Investigation of The Effect of Preoperative Fasting Time on Preoperative and Postoperative Anxiety Levels - Özlem Bilik; Yaprak Sarıgöl Ordin; Zeynep Deveci; Buket Çelik; Emel Sütsünbüloğlu; Özlem Karayurt (Dokuz Eylul University, 2020)
Bacground: It is known that there is fasting after midnight in our country and the duration of the operation is long. This situation is thought to increase the anxiety of patients in the perioperative period. Objectives: To investigate the effect of preoperative fasting duration on preoperative and postoperative anxiety levels. Methods: The study was prospective, cross-sectional and descriptive. The sample consisted of 86 patients who were scheduled for elective surgery in August 2015-January 2016 at the orthopedics and traumatology clinic of the university hospital. Patients were divided into two groups according to fasting period (Group 1 <8 hours; Group 2 ≥ 8 hours). Data were collected with "Sociodemographic and Clinical Characteristics Form" and "State and Trait Anxiety Scale. Descriptive statistics, t test and chi-square tests were used in the analysis of the data. Results: Sociodemographic and clinical characteristics of the groups were similar. The mean fasting time of Group 1 was 7.34 ± 0.18, and that of Group 2 was 12.01 ± 2.10 hours. There was no statistically significant difference between the groups' mean Trait Anxiety Scale score on the day of hospitalization, and the mean preoperative and postoperative State Anxiety Scale scores. Conclusion: Although both groups were found to have mild anxiety before the operation, the duration of fasting did not affect the anxiety level of the patients.